The long-run effects of attending an elite school: Evidence from the UK - Damon Clark; Emilia Del Bono (University of Essex, Institute for Social and Economic Research (ISER), 2014)
This paper estimates the impact of elite school attendance on long- run outcomes including completed education, income and fertility. Our data consists of individuals born in the 1950s and educated in a UK dis- trict that assigned students to either elite or non-elite secondary schools. Using instrumental variables methods that exploit the school assign- ment formula, we find that elite school attendance had large impacts on completed education. For women, we find that elite school attendance generated large improvements in labor market outcomes and significant decreases in fertility; for men, we find no elite school impacts on any of these later-life outcomes.
Keywords: I2; J24; C31; C36; 330; Education; school quality; instrumental variables